Math written production analysis as an assessment strategy and prospective teachers’ knowledge of content and students (Research, Society and Development, 2019)
In this paper, we present potentialities of the use of math written production analysis, as an assessment strategy, to the development of prospective teachers’ knowledge of content and students. For this, some considerations about the mathematical knowledge for teaching are describe and we highlight in this context, the knowledge of the content and the students. Then, in presenting particular aspects of this assessment strategy, we have identified that they can contribute to mobilization/development the prospective teacher’ knowledge as it make possible to know the students way of dealing with mathematical tasks and contents; to get an overview of the most common errors and answers, as well as a class profile with regard to how they deal with the assigned tasks, among others; to reflect on what led the students productions, and why several students have a similar resolution or make the same mistakes; to interpret students' thoughts as expressed in the ways they are able to express them through written production. Thus, in identifying these aspects, we emphasize that the use of math written production analysis as an assessment strategy by preservice mathematics teachers, contributing to mobilization/development of prospective teachers’ knowledge of content and students, can be promising for their teacher education.